2018
DOI: 10.1007/s00280-018-3650-4
|View full text |Cite
|
Sign up to set email alerts
|

Nab-paclitaxel plus S-1 as first-line followed by S-1 maintenance for advanced pancreatic adenocarcinoma: a single-arm phase II trial

Abstract: PurposeWe conducted a single-arm prospective phase II study to determine the efficacy and safety of the first-line treatment of advanced pancreatic cancer with nab-paclitaxel and S-1 followed by S-1 maintenance therapy.MethodsNab-paclitaxel was administered intravenously on days 1 and 8 at 120 mg/m2. S-1 at 120 mg/day (for surface area ≥ 1.5 m2), 100 mg/day (for surface area between 1.25–1.5 m2), and 80 mg/day (for surface area < 1.25 m2) were given two times daily on days 1–14 every 3 weeks. Patients who achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
5
11
1
Order By: Relevance
“…The mPFS rate was 6.2 months (range 4.4–8), and the mOS rate was 13.6 months (range 8.7–18.5). The incidence of grade 3/4 neutropenia was 27.6% [ 13 ], which was similar to our study. In another single-arm, single-center, phase 2 trial, AS and GS were administered to patients with APC.…”
Section: Discussionsupporting
confidence: 91%
“…The mPFS rate was 6.2 months (range 4.4–8), and the mOS rate was 13.6 months (range 8.7–18.5). The incidence of grade 3/4 neutropenia was 27.6% [ 13 ], which was similar to our study. In another single-arm, single-center, phase 2 trial, AS and GS were administered to patients with APC.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, although the above-mentioned retrospective experience confirmed the effectiveness and safety of first-line Gem/NabP in a real world setting, grade 3-4 hematologic toxicity occurred frequently and dose reductions were needed in a higher proportion of patients compared to our report (80% vs. 25%). A recent phase III study analysing NabP plus the oral fluoropyrimidine derivative S-1 followed by S-1 as maintenance treatment for advanced PC patients reported results in terms of ORR (53.1%), median PFS (6.2 months), and OS (13.6 months) similar to our analysis [15]. However, the median age of the study population was much younger (53 vs. 77 years) compared to our report and only 6 patients were over 80 years old.…”
Section: Discussionsupporting
confidence: 88%
“…Two single-arm phase II trials in China reported by Shi et al and Zhang et al showed promising survival (median OS, 9.4-13.6 months) and high ORR (50.0-53.1%) with first-line nab-P/S in patients with advanced PDAC. 13,14 The remarkable results of ORR also indicated the possible role of nab-P/S in the neoadjuvant setting for LAPC. The triweekly regimen of nab-P/S was used in these two trials.…”
Section: Discussionmentioning
confidence: 97%
“…11,12 In two phase II studies in China, the new combination of nab-paclitaxel plus S-1 showed a remarkable ORR of 50.0-53.1% with good OS and favorable safety profiles as first-line therapy for advanced PDAC. 13,14 Hence, we conducted this retrospective study to evaluate the efficacy and safety of first-line chemotherapy with nab-P/S versus nab-P/G in patients with advanced PDAC.…”
Section: Introductionmentioning
confidence: 99%